Effect of biochar on microbial population in heavy metal contaminated soil for 23 years - Sri Yusnaini; Erninda Octalyani; Suskandini Ratih Dirmawati; Abdul Kadir Salam; Iin Purwati Handayani (Universitas Sebelas Maret, 2025)
Soil microbial populations and activities have been repeatedly reported to be severely affected by high concentrations of heavy metals. However, little of this information comes from tropical soil. The fungal and bacterial populations in tropical soils contaminated with heavy metals were observed in a laboratory study. Soils that have been amended once with different rates of heavy-metal-containing waste (0-60 Mg ha-1) in 1998 (23 years ago) were used in this study. We then treated the contaminated soils with different rates of biochar (0-10 Mg ha-1). Biochar is known to significantly reduce heavy metal contaminants through various immobilization reactions. The soil-biochar mixtures were allowed to equilibrate at the soil field water capacity, maintained by a common water reservoir beneath the soil-biochar mixtures, for 4 weeks. After this period, the soil fungal and bacterial populations were counted. The results of the present study showed that high soil levels of Cu and Zn significantly enhanced the fungal population. In contrast, the bacterial population was not affected by the presence of Cu and Zn. In the highly contaminated pots, the addition of biochar significantly enhanced the population of soil fungi (identified as Aspergillus sp.), but it did not affect the population of bacteria. The results of the study suggest that biochar application led to significant enhancement of the population of Aspergillus sp. in pots with high soil Cu and Zn levels, most likely through improved habitat conditions provided by biochar’s porous structure, which could be leveraged in bioremediation efforts for heavy metal-contaminated soils.